ADJUSTMENT OF FIXED ASSETS TO REFLECT PRICE LEVEL CHANGES. - McNichols, Thomas J.; Boyd, F. Virgil (The Accounting Review, 1954)
Abstract The effect of inflation on accounting procedures, and in particular the determination of income, has elicited voluminous literature concerned with the general aspects of the problem. Accountants, in general, have approached the problem with a measure of restraint caused by the confines of basic accounting principles, others have agreed to make the break from conventional accounting practices but have, for the most part, offered nothing more than theoretical considerations while admitting the need for experimentation with methods designed to reflect price level changes. The major emphasis of the problem of measuring real earnings as contrasted to book earnings has centered upon the accounting treatment of two types of assets, inventories and fixed assets. The experimental case study discussed in the article, concerned only with fixed assets, presents a method and indicates the need for adjusting the historical cost of land and depreciable assets and their corresponding depreciation reserve for price level changes. The objective of the presentation is not only to effect a methodology but also to show the significant difference between cost measured in historical dollars and cost measured in units of purchasing power.